Staying connected: implementing avatar robots at schools in Germany and Japan - Spoden, Celia; Ema, Arisa (Frontiers in Digital Health, 2024)
With advancements in communication technologies and internet connectivity, avatar robots for children who cannot attend school in person due to illness or disabilities have become more widespread. Introducing these technologies to the classroom aims to offer possibilities of social and educational inclusion. While implementation is still at an experimental level, several of these avatars have already been introduced as a marketable service. However, various obstacles impede widespread acceptance. Therefore, in our explorative qualitative case study we conducted semi-structured interviews with eight individuals involved in the implementation of the avatar robots AV1 in Germany and eleven participants involved with implementing OriHime in Japan. We analyzed and compared implementation processes, application areas, access and eligibility, and the potential and limitations of avatars at schools. We identified structural similarities and differences in both countries. In the German cases the target is defined as temporary use for children who cannot attend school in person because of childhood illness, with the clear goal of returning to school. Whereas in Japan OriHime is also implemented for children with physical or developmental disabilities, or who cannot attend school in person for other reasons. Our study suggests that avatar technologies bear high potential for children to stay socially and educationally connected. Yet, structures need establishing that grant equal access to avatar technologies. These include educational board regulations, budgets for funding avatar technologies and making them accessible to the public, and privacy protection standards that are adequate, yet do not create implementation hurdles that are too high. Furthermore, guidelines or training sessions on technical, educational and psychosocial aspects of including avatar technologies in the classroom for teachers are important for successful implementation. Since our Japanese cases suggest that expanding the area of application beyond childhood illness is promising, further research on the benefits for different groups is needed.